Internet connectivity disruption in Pakistan (Pakistan) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity mixed detected in Pakistan. Data sourced from IODA, CensoredPlanet.
Censorship Incident ID: PK-2026-0144. Severity: critical. Confidence: 65%